Empowerment: A Theological Perspective - Dickson, C. R. (1994)
It is generally accepted that sound practice must be informed by sound theory. This maxim applies also with reference to the concept empowerment which is in vogue within South Africa today. Therefore it is argued here that for empowerment to be effective it must be underpinned by a sound theological understanding of powerlessness. After exploring the use of the term power (powerlessness), its occurrence and meaning in Psalm 82 is examined, concluding with an attempt at formulating a theological definition of powerlessness.